Análise das potencialidades de uma prática interdisciplinar na formação inicial de professores de ciências da natureza e matemática sobre elementos da Educação CTS - Hiraichi, Harumi Adriane (2023)
This research aims to analyze the knowledge about STS Education (Science, Technology and Society) that is developed and expressed by future teachers - undergraduates - of Natural Sciences and Mathematics in a process of elaboration of a thematic interdisciplinary project in a formative practice that promotes an interdisciplinary training space. For this, in this qualitative research, we were inspired by Content Analysis (CA) to organize and categorize the texts written by the undergraduates in an interdisciplinary project elaborated in a group. Five interdisciplinary projects were analyzed based on a priori categories that deal with the elements of the STS approach, both from a conceptual point of view and from the practices created by the undergraduates. We conclude that characteristic elements of STS Education such as Thematic Approach, Interdisciplinarity and Contextualization were present in all projects, in addition, most of the proposed tasks present real problems in which the themes were broadly covered and advocate the democratization of scientific knowledge. However, none of the works written by the graduates demonstrates to strive with the Latin American Thought in Science, Technology and Society (LATSTS) generally presenting only North American visions of STS Education, which highlights how much LATSTS still distance from initial teacher education.